MANAGEMENT OF KUIN RIVER USING THE ECO-HYDRAULIC APPROACH - Parida Angriani; Akhmad Munaya Rahman; Karunia Puji Hastuti (Universitas Lambung Mangkurat, 2021)
River management using the eco-hydraulic approach is aimed at preserving the ecological components in the river environment through hydraulic engineering. This study aims to identify the existing conditions on Kuin River border, analyze the relationship and influence of community activities on the banks of Kuin River on the water quality of Kuin River, and study the river development pattern with the concept of eco-hydraulic on Kuin River. Data were collected based on the results of field surveys and laboratory tests for water and soil. The results showed that the current condition of the riverbank of Kuin River has not fulfilled its function as a buffer space between the river and the mainland, due to the large number of community settlements rather than vegetation that functions to protect the river. Kuin River is polluted because several ecological indicators such as pH, Fe, BOD, and COD have exceeded the maximum allowable limits. This occurs due to social activities and development along the river, which have an impact on biotic and abiotic aspects of the river. The type of soil on the banks of the Kuin River is silt mixed with clay with moderate to high plasticity. Based on this condition, there is an assumption that the cliffs on the banks of Kuin River have the potential for landslides. Therefore, a pattern for developing cliff protection using riverbank vegetation components is recommended